Formalization of hydrocarbon conversion scheme of catalytic cracking for mathematical model development; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Nazarova G. Yu. Galina Yurievna; Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Kiseleva S.; Stebeneva V. (Latest Technology of Oil-and-Gas Pipelines and Petroleum Storage, 2015)
Title screen